ANALISIS FAKTOR YANG BERPENGARUH DALAM PENERAPAN KONSEP GREEN PADA BANGUNAN FLOUR MILL PLANT MENGGUNAKAN SEM-PLS - Iwan Kurniawan; Albert Eddy Husin (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
The Main Building of the Flour Mill Plant is the main part of the wheat flour mill consisting of Wheat Bins, Process Area, Finish Bins, Laboratory, and Buck Loading Area. The construction of factory buildings that apply the Green concept is urgently needed, this is to the mission of the Sustainable Development Goals 2030, that by 2030 the new development will have a concept of 100% and an existing building of 60%. To reduce the environmental burden on an industry, it is necessary to build and develop a factory building with a green concept. The Implementation of the Green Concept to the Main Building of the Flour Mill Plant using Structural Equation Modeling – Part Least Square (SEM-PLS). The result of this study is that there are